Ascariasis among Orang Asli children at Pos Lenjang, Pahang, Malaysia - Hartini Y; Mohamed Kamel AG (Penerbit UKM, 2010)
A cross-sectional study was carried out in 2006 to determine the prevalence of Ascaris lumbricoides infection among Orang Asli (aborigines) children in Pos Lenjang, Pahang. A total of 71 faecal samples were collected from the children (40 girls and 31 boys) aged between 1-12 years. The samples were examined for the presence of the ova of A. lumbricoides using direct faecal smear and formalin-ether concentration techniques. The results revealed that the overall prevalence of A. lumbricoides infection was 42.3%. The prevalence of A. lumbricoides infection was found to be slightly higher in males (45.2%) compared to females (40%) (p>0.05). The school-aged children showed higher prevalence of infection (48.6%) as compared to the preschool children (35.3%) (p<0.05). The high prevalence of A. lumbricoides infection in these Orang Asli children was associated with low socioeconomic status, poor environmental sanitation and personal hygiene. In the 30 samples positive for Ascaris ova , a detection rate of 100% was recorded using the formalin-ether concentration technique as compared to 46.7% with the direct smear technique (p<0.05). Thus, it is recommended that both techniques (the direct smear and concentration techniques) should be performed routinely for a more accurate diagnosis